Ang Dalubhasa - Poe, Fernando, Jr.; Medved, Nanette; Fernandez, Maritoni; Reyes, Ronwaldo; Millennium Cinema (Firm). ([Place of production not identified] Millennium Cinema, 2010)
Jaime de Guzman, a military neurosurgeon, survives a massacre that killed his wife and daughter. He hunts down all perpetrators and is able to kill them except the boss. From returning to a normal life and to the death of a girl after performing a brain operation to her, he hides his guilt to his new life. - Written by cinesum
Summary taken from: https://www.imdb.com/title/tt0344838/?ref_=fn_al_tt_1
Story, Fernando Poe Jr, screenplay, Pablo S. Gomez, storExecutive producers, Orly Ilacad, Marvic C. Sotto, Antonio P. Tuviera ; story and screenplay, Marvic C. Sotto, Tony Y. Reyes, Bibeth Orteza ; musical director, Jesse Lasaten ; director, Tony Y. Reyes.
Fernando Poe, Jr., Nanete Medved, Maritoni Fernandez.
Keywords: Ang Dalubhasa (Motion picture).; Action